Priming shoppers’ well-being goal in grocery stores: Moving toward healthier food choices? - Luomala, Harri T.; Järvinen, Sari; Peltola, Johannes; Pennanen, Kyösti; Sihvonen, Jenniina (Elsevier, 2023)
At the times of obesity epidemic, innovative ways to nudge food shoppers toward healthier choices are needed. Key ideas from the conceptual metaphor processing, food symbolism and contextual priming literatures are synthetized to argue for the idea that visual, olfactory and gustatory cues can activate shoppers’ well-being goal and guide their in-store movements and healthy food purchasing behaviors. Two field experiments, separated by an 8-month interval, are conducted in the same grocery store. The results show that priming the well-being goal in real store can push consumers to move toward spots where healthier options are available – materializing also into greater sales of yogurts, vegetables and heart healthy-labeled products. Counterintuitively, the well-being goal activation possibly first facilitate approaching indulgent foods. Yet, the actual sales of palatable foods such as ice cream and minced beef meat may in fact diminish. This research spurs numerable academic and practical implications.
Keywords: Consumer goal activation; Field experiment; Healthy food sales; Priming; Shopper movements; fi=Markkinointi|en=Marketing|